The Scientific Rationale for the Introduction of Renalase in the Concept of Cardiac Fibrosis - Stojanovic, Dijana; Mitic, Valentina; Stojanovic, Miodrag; Milenkovic, Jelena; Ignjatovic, Aleksandra; Milojkovic, Maja (Frontiers in Cardiovascular Medicine, 2022)
Cardiac fibrosis represents a redundant accumulation of extracellular matrix proteins, resulting from a cascade of pathophysiological events involved in an ineffective healing response, that eventually leads to heart failure. The pathophysiology of cardiac fibrosis involves various cellular effectors (neutrophils, macrophages, cardiomyocytes, fibroblasts), up-regulation of profibrotic mediators (cytokines, chemokines, and growth factors), and processes where epithelial and endothelial cells undergo mesenchymal transition. Activated fibroblasts and myofibroblasts are the central cellular effectors in cardiac fibrosis, serving as the main source of matrix proteins. The most effective anti-fibrotic strategy will have to incorporate the specific targeting of the diverse cells, pathways, and their cross-talk in the pathogenesis of cardiac fibroproliferation. Additionally, renalase, a novel protein secreted by the kidneys, is identified. Evidence demonstrates its cytoprotective properties, establishing it as a survival element in various organ injuries (heart, kidney, liver, intestines), and as a significant anti-fibrotic factor, owing to its, in vitro and in vivo demonstrated pleiotropy to alleviate inflammation, oxidative stress, apoptosis, necrosis, and fibrotic responses. Effective anti-fibrotic therapy may seek to exploit renalase’s compound effects such as: lessening of the inflammatory cell infiltrate (neutrophils and macrophages), and macrophage polarization (M1 to M2), a decrease in the proinflammatory cytokines/chemokines/reactive species/growth factor release (TNF-α, IL-6, MCP-1, MIP-2, ROS, TGF-β1), an increase in anti-apoptotic factors (Bcl2), and prevention of caspase activation, inflammasome silencing, sirtuins (1 and 3) activation, and mitochondrial protection, suppression of epithelial to mesenchymal transition, a decrease in the pro-fibrotic markers expression (’α-SMA, collagen I, and III, TIMP-1, and fibronectin), and interference with MAPKs signaling network, most likely as a coordinator of pro-fibrotic signals. This review provides the scientific rationale for renalase’s scrutiny regarding cardiac fibrosis, and there is great anticipation that these newly identified pathways are set to progress one step further. Although substantial progress has been made, indicating renalase’s therapeutic promise, more profound experimental work is required to resolve the accurate underlying mechanisms of renalase, concerning cardiac fibrosis, before any potential translation to clinical investigation.